O futebol para sócios torcedores: análises sobre um jogo mercantilizado - Mauro Lúcio Maciel Júnior (2023)
The objective of this study was to analyze the relationships established with Galo na Veia, by a group of fans associated with the PST of Clube Atlético Mineiro. To this end, I aimed to: present the social and cultural conditions in which fan membership programs are manifested; describe the trajectory of CNG and the services it offers throughout its history; present a profile of the fan members studied, analyze the uses they reported making of Galo na Veia and know their understanding of the model represented by fan member programs. Such choices resulted from the fact that I observed the relationships between fans and PST, in terms of the interactions of production and reception of a cultural product, based on the encoding and decoding model developed by Stuart Hall. In this sense, I developed an investigation supported by the combination of bibliographical, documentary and field research, with the purpose of obtaining the necessary subsidies to achieve the goals outlined for the investigation. When performing these procedures, I compiled studies related to the hyper-commodification scenario that permeates football, sports and contemporary life; I gathered and analyzed documents that allowed me to present the history and structure of the GNV constitution; I compared and analyzed the data generated by 141 questionnaires and 15 semi-structured interviews carried out with a group of Atletico fan members. As a result of these actions, I worked with the idea that the historical moment that shelters the emergence and consolidation of fan membership programs can be recognized in terms of what Gilles Lipovestsky calls the hyperconsumption society, whose installation dates back to the end of the 1970s. Extending into contemporary times, this period has provided, in the sports field, the intensification of commercial activities linked to the sector. Inserted in this context, Galo na Veia was launched in 2012, characterized as an instrument for establishing a commodified relationship between Atlético and its fans. Featuring different configurations throughout its history, the program has offered benefits ranging from easy access to games, to privileges for purchasing products and/or services from CAM partners. Regarding the ways in which CNG is used, the advantages linked to obtaining tickets are the best known, searched and used by fans. In this sense, there is a characterization of a reading aligned with the commercial logic of the program's production. However, when observing the members' understandings, it is noted, in general, a negotiated vision, which combines senses of agreement and opposition to the model implemented by the PSTs. In this context, the biggest contradictions expressed by the subjects concerned the elitization of football and the exclusion of poorer sections of the fans. As final considerations, I point out the importance of the study for understanding consumption as a complex phenomenon, as well as the need and importance of developing new empirical investigations on the subject, in order to better understand the different particularities related to the topic.